A glimpse on health care financing in Nepal - Subedi, Khem Raj (Journal of Tikapur Multiple Campus, 2018)
This article highlights the important components of Nepalese healthcare financing and aims at examining the health care financing system in Nepal in terms of share of government health care expenditure per capita, household out-of-pocket expenditure, and ratio of total health care expenditure to Gross Domestic Product (GDP). The recent data shows that Government of Nepal allocates meagre 1.11 percent of GDP from government coffer for health care financing where out-of-pocket payment is 3.47percent of GDP and it is about 60 percent of total health care expenditure. It implies that people are heavily dependent on their own source for health care financing. Public Health Expenditure as a percent of Total Health Expenditure 40 percent. Public Expenditure on health as Percent of Total Government Expenditure is 11 percent, Total Health Expenditure (government and out-of-pocket) is 5.8 percent of GDP. The annual per capita government health care expenditure is US$ 44 for 2015. This figure is extremely low in comparison to the other parts of the world like European Union US$ 2192, Western Pacific Region US$ 1338, American Region US$ 1192 even African Region US$114 and South East Asian Region US$ 175 for the same period. This infers that the health care financing in resource-poor country like Nepal relies heavily on household out-of-pocket payments which often results in financial catastrophe for poor and economically vulnerable households. The government needs to make serious effort to bring drastic change in policy priority to improve health care financing to ensure quality change in this sector taking into consideration allocative efficiency and technical efficiency the essential parameters to ensure efficiency in health care financing schemes.